PENGARUH KEPEMIMPINAN, DISIPLIN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SRAGEN - Aji, Ambyah Atas Aji; Maulana, M Guntur; Candrakusuma, Desy Amalia (FAKULTAS EKONOMI UNWIDHA KLATEN, 2025)
This study aims to determine the effect of leadership, work discipline and work motivation on the performance of employees of the Population and Civil Registration Office of Sragen Regency both partially and simultaneously. This research is quantitative research. The sampling technique uses the census technique by taking the entire existing population. The population of this study were 50 respondents who were all ASN and THL employees at the Population and Civil Registration Office of Sragen Regency. The analysis techniques used are research instrument test, hypothesis testing, classical assumption test, multiple linear regression analysis, and coefficient of determination (R²). Multiple linear regression test results Y = 9.715 + 0.378X1 + 0.510X2 + 0.435X3. The results of the t test of the leadership variable on employee performance obtained the t value (4,423)> from the t table (2,013) and the resulting significant value of 0.000 which is smaller than 0.05 which means that leadership partially has a positive effect on employee performance. The t test results of the work discipline variable on employee performance obtained the t value (5.234)> from the t table (2.013) and the resulting significant value of 0.000 which is smaller than 0.05 which means that work discipline partially has a positive effect on employee performance. The results of the t test of the work motivation variable on employee performance obtained the t value (4,806)> from the t table (2,013) and the resulting significant value of 0.000 which is smaller than 0.05, which means that work discipline partially has a positive effect on employee performance.